The Lexical Ambiguity in News Headlines of BBC World: Semantics Study - Intan Cezya Sijabat; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study investigates lexical ambiguity in the headlines of BBC World News by employing a media ethnography approach within qualitative research. Lexical ambiguity, particularly in the form of homonymy and polysemy, often arises in news headlines due to their concise and attention-grabbing nature. Such ambiguity can lead to multiple interpretations and potentially mislead readers, especially those who rely solely on the headline without reading the full article. The primary data consist of BBC World headlines published between 2023 and 2024, which were selected purposively based on their potential to contain ambiguous lexical items. Using semantic theories from Kreidler and Lyons, along with Roland Barthes’ semiotic model, the study classifies types of ambiguity and analyzes the denotative and connotative meanings embedded in each headline. The findings reveal that many BBC headlines contain ambiguous terms that require contextual and cultural knowledge for accurate interpretation. This research highlights how ambiguity functions not only as a linguistic phenomenon but also as a discursive strategy that reflects media ideology and influences public perception. The study contributes to linguistic and media literacy scholarship by encouraging critical awareness of language use in global news discourse.